Corporate Sosial Responsibility and Firm Value: The Mediating Role of Profitability and Governance - Hana Afifah Fauziah; Estu Widarwati; Nunik Nurmalasari; Tigin Lugiani (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2023)
TFirm value is a value that can be observed through stock prices by investors and one of the factors that affect it is corporate social responsibility (CSR). This study aims to find empirical evidence regarding the relationship of CSR to firm value by using profitability and corporate governance as moderating variables as a novelty value in this study. We use CSRDI as measurement of CSR and firm value proxied by Tobins’Q, then managerial ownership for corporate governance proxy, and Return on Asset (ROA) for profitability proxy. The sample is 10 non-financial companies on the Indonesia Stock Exchange (IDX) from 2015 to 2021 included consumer non cyclical, industrial, energy, basic material, and infrastructure sector. We analyzed the datas using panel data regression and also moderating regression analysis (MRA) for the test the hyphoteses. The results indicate that CSR has a positive effect on firm value and profitability significant moderate the relation of CSR and firm value, while corporate governance has no moderating role. We also find significant role of firm size as control the relation of CSR, Firm Value, Profitability, and Governance. It important to manage the efficiency of asset management for improving firm value linked to CSR decision.